Analysis of the current state and modern trends in the development of the rocket and space complex of the Russian Federation - E. V. Chernyaev (Интеллект. Инновации. Инвестиции)
This article focuses on the analysis of the current state and modern development trends of the Russian Federation’s rocket and space complex under contemporary conditions. The relevance of the study is driven by the increasing complexity of geopolitical and sanctions policies, which affect technological development in the industry, as well as the significant role of the rocket and space complex in ensuring national security, scientific progress, and the country’s technological sovereignty. The research is aligned with the Russian Space Activity Development Strategy up to 2030 and beyond.